Pengaruh Gaya Kepemimpinan Transformasional dan Kompensasi terhadap Prestasi Atlet Tingkat Nasional Dengan Motivasi sebagai Variabel Interverning pada Dinas Pemuda dan Olahraga Provinsi Jambi - Helen Helen (Universitas Batanghari, 2023)
The results of the research variable Transformational leadership style, compensation, motivation and achievement of athletes in the Jambi Province Youth and Sports Service using a sample of 81 respondents. Transformational leadership style (X1), Compensation (X2), motivation (Y) and Athlete achievement (Z) at the Jambi Province Youth and Sports Service, where Transformational leadership style is in the very good category, Compensation is in the good category, Athlete motivation and achievement are in the high category. Compensation has a significant effect on motivation. Therefore, it can be concluded that compensation (X2) partially has a significant effect on motivation (Y). Transformational and Compensational leadership styles together influence motivation. Therefore, it can be concluded that the results of testing Transformational and Compensatory leadership styles simultaneously have a significant influence on motivation. Transformational and Compensational leadership styles together have a significant effect on athlete performance. Therefore, it can be concluded that the test results are significant, which means Transformational and Compensational leadership styles simultaneously have a significant influence on athlete achievement. Motivation has a significant effect on athlete achievement. Therefore, it can be concluded that motivation partially has a significant effect on athlete achievement.